Kostogruz S.G., Misliborskij V.V.. Mechanical modeling oscillating systems - Костогриз, С. Г.; Мисліборський, В. В. (Problems of Tribology, 2018)
The paper considers general approaches and principles of constructing calculation models of mechanical vibrational systems, as well as a method for their simplification and determination of consolidated masses and torsional stiffnesses